Komplikasi Sistemik Pada Pasien Diabetes Melitus Tipe 2 - Ririn Dwi Saputri (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Diabetes mellitus is one of the main health problems in people who have long and short term complications. The prevalence of Diabetes Mellitus in Indonesia in 2018 is 8.5%, in Lampung 1.4%. Patients suffering from diabetes mellitus only realize the danger of this disease after various complications that arise both acute and chronic. Purpose of the research is to know profile of systemic complications in type 2 diabetes mellitus patients at Pertamina Bintang Amin Hospital in Bandar Lampung.Methods: This research uses a descriptive survey method with a cross-sectional approach. This research was conducted in February 2020 by taking medical record data on type 2 diabetes mellitus patients at Pertamina Bintang Amin Hospital in Bandar Lampung in 2019. Results: Subjects in the study were 72 patients. Analysis of the data used in this study is univariate analysis. Frequency distribution based on acute complications of KAD in 6 patients (8.3%), hypoglycemia in 8 patients (11.1%). Microvascular complications were retinopathy in 8 patients (11.1%), nephropathy in 11 patients (15.3%), neuropathy in 5 patients (6.9%). Macrovascular complications were cerebrovascular 3 patients (4.2%), coronary heart disease 8 patients (11.1%), and ulcers of 20 patients (27.8%). Conclusion: Frequency distribution based on complications, of the 72 people studied, the majority of patients experienced complications, as many as 43 people (59.7%)